The Rhetoric of Duality - Quirino Paris; Michael R. Caputo (Journal of Agricultural and Resource Economics, 1995)
Agricultural economists' view of duality has often assumed the characteristics of an ambivalent relation. During the eighties, several authors published papers which put in doubt this or that aspects of duality. This study emphasizes the notion that duality is a time-honored approach suitable for solving problems that can be expressed mathematically. Contrary to many assertions that appeared in the agricultural economics literature, duality does not seem to suffer from any theoretical limitations any more than does the formulation of the primal problem. The article presents two problems that can be solved with dual methods. The authors are incapable of deriving the same results using primal approach.